Ações de extensão rural da Emater-RS/Ascar no âmbito do programa de fomento às atividades produtivas rurais do Plano Brasil Sem Miséria executadas em comunidades quilombolas - Menegon, Mariane Roman (2023)
This dissertation aims to gather and systematize rural extension initiatives aimed at promoting food security and combating poverty, carried out by Emater-RS/Ascar in remaining Quilombola communities within the scope of the Rural Productive Activities Promotion Program of the Brazil Without Misery Plan. It is a qualitative exploratory study conducted through the technique of documentary research. The analyzed documents were the Technical Assistance and Rural and Social Extension Activity Reports from Emater-RS/Ascar, available on the institution's official website, spanning from 2013 to 2023, encompassing the phases of the Rural Productive Activities Promotion Program of the Brazil Without Misery Plan. The analysis focused on the actions and activities developed by the institution with remaining Quilombola communities, particularly within the framework of programs fostering social and productive inclusion, highlighting Technical Assistance and Rural Extension actions in Brazil's Quilombola communities. The theoretical framework is based on the history of Technical Assistance and Rural Extension in Brazil, as well as concepts regarding Traditional Peoples and Communities and their everyday struggle for social rights. Furthermore, it discusses public policies for overcoming rural poverty and ensuring food security within the context of the aforementioned program, actions, and the informed public, as well as Rural Extension activities in remaining Quilombola communities carried out by Emater-RS/Ascar. It is emphasized that Technical Assistance and Rural Extension constitute a policy aimed at developing rural communities, aiding in poverty alleviation through social and productive inclusion and the promotion of food and nutritional security. As a result of this study, it is noted that the Rural Productive Activities Promotion Program acted as an enhancer of Technical Assistance and Rural and Social Extension actions with these communities. The analysis underscores the need for professional qualification of extension workers and adequate public investment in policies that positively impact the lives of people in remaining Quilombola communities.